Changes in symptom pattern in Meniere's disease by duration: the need for comprehensive management - Pyykkö, Ilmari; Zou, Jing; Vetkas, Nora (Frontiers in Neurology, 2024)
PurposeThis retrospective study aimed to analyze the symptom profile of Meniere's disease (MD) patients, particularly focusing on the cessation of episodic vertigo and the disease's longitudinal course and the impact of major symptoms on quality of life (QoL).MethodsThe study employed a cross-sectional design and was conducted on 365 out of 560 individuals with definite MD from the Finnish Vestibular and Meniere Federation, utilizing an internet-based questionnaire. Participants were surveyed on vertigo attacks, vestibular drop attacks (VDA), balance issues, selective cognitive complaints, hearing loss, and their effects on overall quality of life (QoL). The study population comprised 79.5% females and 20.5% males, with a mean age of 63 years and an average disease duration of 15.2 years.ResultsThe onset of MD was characterized by simultaneous hearing loss, vertigo, and tinnitus in 38% of participants. There was a significant delay in diagnosis for many, with 20% experiencing a delay of over 5 years. The frequency and duration of vertigo attacks generally decreased over time, with attacks becoming shorter and less severe as the disease progressed. Spontaneous remission from episodic vertigo occurred in 34% of participants variably throughout the course of MD. Of the participants 65.5% reported balance issues, and 34% experienced mild VDAs, with severe falls occurring in 10%. VDAs were more common with longer disease duration. Bilateral hearing loss developed in 34.5% of participants over the long term, with a higher risk associated with younger onset age, migraines, and family history of MD. Fatigue, anxiety, and depression were prevalent, particularly among younger participants. Cognitive impairments were linked to the severity of these symptoms and the presence of constant dizziness. QoL was significantly lower among participants with constant dizziness, with factors like fatigue, depression, VDA, and hearing loss contributing to this reduction.ConclusionsThe study highlights the complexity of MD. While vertigo may spontaneously remit, other symptoms such as VDAs, balance issues, cognitive complaints, and hearing loss often persist and worsen over time. Assessing MD solely on primary symptoms like vertigo and hearing loss is insufficient; a comprehensive evaluation is necessary for effective management.